CEO Demographics and Corporate Cash Holdings: Evidence from Banking Companies in Indonesia - Firmansyah, Amrie; Kartiko, Nafis Dwi (Universitas Negeri Semarang, 2024)
Purpose: The study examines the impact of CEO demographics on corporate cash holdings in the Indonesian banking industry, focusing on CEO tenure, age, education, and gender. The study considers how regulatory constraints, firm characteristics, and macroeconomic factors shape corporate liquidity decisions. Method: Using data from 46 banking companies listed on the Indonesia Stock Exchange (IDX) from 2004 to 2022, this study analyzes 637 firm-year observations. The Ordinary Least Squares (OLS) regression model assesses the relationship between CEO demographics and cash holdings, incorporating firm-specific and macroeconomic control variables such as firm size, leverage, working capital, inflation, and GDP growth. Findings: The result reveals that CEO tenure negatively affects corporate cash holdings, suggesting that longer-tenured CEOs may optimize liquidity management rather than hold excess cash. CEO education positively influences cash holding, reflecting a stronger understanding of financial management and risk mitigation. In contrast, CEO age shows an insignificant effect, implying that experience and strategic priorities may matter more than age alone. Female CEOs exhibit a negative influence on cash holdings, possibly due to a more cautious financial approach or external governance expectations. Novelty: The study contributes to the literature on corporate liquidity by integrating CEO demographic factors with firm-specific and macroeconomic contexts. It extends the application of the upper echelons theory in a highly regulated sector, demonstrating how leadership traits influence cash management decisions. The research offers valuable insights for regulators, investors, and corporate boards in evaluating CEO profiles when assessing financial policies and risk management strategies.